Pertumbuhan dan Produksi Rumput Odot (Pennisetum purpureum cv. Mott) pada Tanah Entisol di Lahan Kering Akibat Pemberian Pupuk Organik Cair Berbahan Feses Babi Dengan Volume Air Berbeda - Celeste De Araujo; Maria Yasinta Un; Bernadete Barek Koten; Melkianus D. S. Randu; Redempta Wea (Jurnal Ilmu Peternakan Terapan, 2019)
This study aims to examine the growth and production of odot grass (Pennisetum purpureum cv. Mott) on entisol soils with different amounts of water volume in Liquid Organic Fertilizer (LOF) made of pig feces. This research was carried out for 5 months in the feed garden of Noelbaki Village and State Agricultural Polytechnic of Kupang. The study used completely randomized design (CRD) with 5 treatments consisting of P0 (without LOF), P1 (LOF without water), P2 (LOF 1 L with 2 L water solvent), P4 (LOF 1 L with 4 water solvent) L), and P6 (LOF 1 L with 6 L water solvent) repeated 4 times. The observed variables were plant height increase, number of buds, chlorophyll content (mg/mL), absorption of nitrogen (g/polybag), fresh and dried production. The data were analyzed by ANOVA and Duncan Multiple Range Test. The results showed that dilution of LOF used different water volumes had a non-significant effect (P>0.05) on the number of buds (average of 0.27 buds/week), but had a significant effect (P<0.05) to increase plant height (average of 4.45 cm/week), chlorophyll content (average of 20.42 mg/mL), absorption of nitrogen (average of 0.16 g/polybag), fresh production (average of 40.09 g/polybag) and dried production (average of 10.83 g/polybag). The best level was 1 L POC which was diluted in 2 L water.